Study on microscale flow characteristics of electrorheological Fluids. Issue 5 (January 2021) - Zhu, Shisha; Lei, Xianhua
Abstract: Electrorheological fluid is a kind of intelligent material whose rheological properties change rapidly and reversibly under the action of external electric field, It has a broad prospect in practical engineering application. It is found in the research progress of electrorheological fluids. The time scale and space scale of the electrorheological effect are very small, and the flow process has some micro-scale flow characteristics. In this paper, the dynamics of dielectric particles in electrorheological fluids under static and dynamic coupling fields is numerically simulated by dissipative particle dynamics method. The influence of surface force under static field on the submicrostructure of Electrorheological fluid and the influence of electroviscosity under dynamic coupled field on the flow rate of Electrorheological fluid are also studied.